Strength training in youth soccer players: towards an optimal relationship between load magnitude and performance enhancement - Magallanes, Adrián; Parodi, Andres; Magallanes, Carlos; Gonzalez-Ramírez, Andrés (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
In soccer, sprinting speed and vertical jump are critical skills to achieve high performance. Controversy exists about which type of training is most appropriate to improve these skills in youth players with no previous experience in programmed strength training. The aim of this study was to evaluate the efficacy and efficiency of a 16-week programme of resistance (weight) and plyometric training on sprinting and vertical and horizontal jumping in male youth soccer players. The study involved 18 soccer players, 14.1 ± 0.3 years old, with no previous experience in programmed strength training. They performed a combined cycle of resistance and plyometric training on different days, twice a week, respectively. Before and after the experimental intervention, the athletes were tested in countermovement vertical jump, bipodal horizontal jump, unipodal horizontal jump and 30 m linear sprint. After the intervention, significant improvements were observed in all the variables analyzed (p ≤ 0.05). Given that the relationship between the improvement in performance and the magnitude of the loads applied was shown to be superior to other similar interventions, it is possible to conclude that this type of training programme is both effective and efficient in the population studied.